Pentecost and the World: Roland Allen, the Spirit, and Remodeling Twenty-First-Century Mission. (July 2020) - Oxbrow, Mark
A century after his major publications, Roland Allen continues to attract attention within the mission community. He has much to say to contemporary perceptions that new models in mission are urgently required. Allen is less concerned with methods than with the spiritual impulse for mission and the biblical principles by which it is lived. The missionary Spirit of Christ is at the heart of all mission, and the Pauline principles that Allen advances derive from our response to that Spirit. Following Allen, this article challenges a number of accepted contemporary practices in mission, asking "Is Christ here being revealed?"